2012
DOI: 10.1038/ncomms1665
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the carboxy-terminal flanking region of a universal influenza epitope alters CD4+ T-cell repertoire selection

Abstract: Human CD4+ αβ T cells are activated via T-cell receptor recognition of peptide epitopes presented by major histocompatibility complex (MHC) class II (MHC-II). The open ends of the MHC-II binding groove allow peptide epitopes to extend beyond a central nonamer core region at both the amino- and carboxy-terminus. We have previously found that these non-bound C-terminal residues can alter T cell activation in an MHC allele-transcending fashion, although the mechanism for this effect remained unclear. Here we show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
45
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 45 publications
2
45
0
Order By: Relevance
“…These data show that a range of different modifications to PFRs could modulate specific CD4 + T cell responses including amino acids with biochemically distinct side chains (52, 53). The identification of these PFR amino acid enrichment patterns suggests that they play a role during CD4 + T cell activation and can modulate antigen recognition.…”
Section: Modulating Cd4+ T Cell Responses Via Altered Peptide Flankinmentioning
confidence: 81%
See 1 more Smart Citation
“…These data show that a range of different modifications to PFRs could modulate specific CD4 + T cell responses including amino acids with biochemically distinct side chains (52, 53). The identification of these PFR amino acid enrichment patterns suggests that they play a role during CD4 + T cell activation and can modulate antigen recognition.…”
Section: Modulating Cd4+ T Cell Responses Via Altered Peptide Flankinmentioning
confidence: 81%
“…The identification of these PFR amino acid enrichment patterns suggests that they play a role during CD4 + T cell activation and can modulate antigen recognition. Further studies using antigen specific CD4 + T cell clones demonstrated that PFR modifications could enhance CD4 + T cell activation (53). Although a wide range of different amino acid substitutions in PFRs could generate stronger CD4 + T cell responses, we observed that basic residues at the peptide C-terminus, or acidic residues in the N-terminus, were most commonly enriched and generated enhanced CD4 + T cell responses across different MHC-II alleles and different peptides.…”
Section: Modulating Cd4+ T Cell Responses Via Altered Peptide Flankinmentioning
confidence: 99%
“…In humans, HLA variation is expected to influence the identity of immunodominant and immunoprevalent antigens in specific individuals. Model systems have identified additional factors controlling epitope choice for CD4 T cells, including naïve T-cell repertoire (5), antigen abundance (6), antigen folding (7), protease processing and epitopeflanking regions (8), and antigenic competition (9).…”
mentioning
confidence: 99%
“…Nonetheless, the epitope-specific CD4 TCC 7 and 53 did not recognize the nonaHHV orthologous peptides at low concentrations. All nonreactive peptides diverged from the aHHV conserved epitope at HLA-II anchor residues P4, P6, and P9 (43,57). Possibly, the peptides are unable to form stable peptide:HLA-DR complexes or do not functionally engage with the TCR of both TCC.…”
Section: Discussionmentioning
confidence: 99%
“…Immunogenicity of pathogen-derived proteins is determined by various factors including the host T cell repertoire, Ag abundance, size and structure, antigenic competition, and Ag processing (57)(58)(59). VZV IE62 and HSV ICP4 are abundantly expressed viral proteins that are transported from the nucleus to the cytoplasm for incorporation in the tegument of the virion during lytic infection (27,(60)(61)(62).…”
Section: Discussionmentioning
confidence: 99%